2012
DOI: 10.3168/jds.2011-4650
|View full text |Cite
|
Sign up to set email alerts
|

Low progesterone concentration during the development of the first follicular wave reduces pregnancy per insemination of lactating dairy cows

Abstract: Objectives were to determine the effect of progesterone (P4) concentration on fertility of lactating dairy cows induced to ovulate follicles of the first follicular wave. Lactating dairy cows (n=989) at 38±3d postpartum were balanced by parity and body condition score and randomly assigned to 3 treatments: first follicular wave (FFW), first follicular wave with exogenous P4 (FFWP), or second follicular wave (SFW). All cows had their estrous cycle presynchronized with 2 injections of prostaglandin (PG) F(2α) gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 38 publications
7
68
1
5
Order By: Relevance
“…Bisinotto et al (2013) observed that incorporating Bisinotto, Ribeiro and Santos 154 two CIDR inserts during the timed AI protocol for cows without CL increased concentrations in plasma to 2.65 ng/mL and restored fertility similar to that of cows in dioestrus when the timed AI was initiated. Similar findings had been observed by Lima et al (2009b) and Denicol et al (2012). Therefore, when supplemental progesterone has to be used in high-producing cows, it is suggested that benefits to P/AI will be greater when the resulting concentrations of progesterone in blood resemble those of cows in dioestrus and, in some cases, two intravaginal devices are needed to achieve such concentrations.…”
Section: Optimising Timed Ai Programmessupporting
confidence: 65%
See 4 more Smart Citations
“…Bisinotto et al (2013) observed that incorporating Bisinotto, Ribeiro and Santos 154 two CIDR inserts during the timed AI protocol for cows without CL increased concentrations in plasma to 2.65 ng/mL and restored fertility similar to that of cows in dioestrus when the timed AI was initiated. Similar findings had been observed by Lima et al (2009b) and Denicol et al (2012). Therefore, when supplemental progesterone has to be used in high-producing cows, it is suggested that benefits to P/AI will be greater when the resulting concentrations of progesterone in blood resemble those of cows in dioestrus and, in some cases, two intravaginal devices are needed to achieve such concentrations.…”
Section: Optimising Timed Ai Programmessupporting
confidence: 65%
“…Incorporation of intravaginal controlled internal drug release (CIDR) containing progesterone during presynchronisation did not result in significant changes in fertility (Chebel et al, 2006, Rutigliano et al, 2008. Overall, lactating dairy cows subjected to PGF 2α -based presynchronisation programmes had 42% greater odds of becoming pregnant compared with cows that did not receive any presynchronisation before the timed AI protocol (odds ratio (OR) = 1.42, 95% CI = 1.23 to 1.64; Bisinotto and Santos, 2012).…”
Section: Optimising Timed Ai Programmesmentioning
confidence: 99%
See 3 more Smart Citations